A Comparative Study: Completion of Fine Motor Office Related Tasks by High School Students with Autism Using Video Models on Large and Small Screen Sizes. - Mechling, Linda; Ayres, Kevin (Journal of Autism & Developmental Disorders, 2012)
The purpose of this investigation was to compare fine motor task completion when using video models presented on a smaller screen size (Personal Digital Assistant) compared to a larger laptop screen size. The investigation included four high school students with autism spectrum disorders and mild to moderate intellectual disabilities and used an adapted alternating treatments design with baseline, extended baseline, comparison, and final treatment conditions. Results showed that although independent completion of fine motor office related tasks increased under both procedures, use of video models on the larger screen resulted in a higher percentage of correct responses across all four students.